Strategi Penerapan Hazard Analysis and Critical Control Point Dalam Mengendalikan Potensi Bahaya Udang Beku Pada Metode Contact Plate Freezer di PT Dachan Mustika Aurora Tarakan - Sudirman Sudirman; Mariam Mariam; Sulkifli Sulkifli (KAMPUS AKADEMIK PUBLISING, 2026)
Frozen shrimp is one of the fisheries commodities that is vulnerable to potential Frozen shrimp is one of the fishery commodities that is susceptible to biological, chemical, and physical hazards during processing. The implementation of the Hazard Analysis and Critical Control Point (HACCP) system is essential to ensure food safety, particularly in frozen shrimp processed using the Contact Plate Freezer (CPF) method. This study aimed to analyze the implementation of HACCP and formulate strategies for controlling potential hazards in frozen shrimp processed using the Contact Plate Freezer (CPF) method. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The data were analyzed based on the seven principles of HACCP and a SWOT analysis. The results indicated that the major potential hazards included microbiological contamination, antibiotic residues, and physical contaminants such as metal fragments and other foreign materials. The Critical Control Points (CCPs) were identified at the raw material receiving stage and the metal detector process. Critical limits, monitoring procedures, corrective actions, verification activities, and record-keeping were implemented consistently and systematically, ensuring the safety of frozen shrimp processed using the Contact Plate Freezer (CPF) method. Furthermore, the SWOT analysis generated appropriate strategic recommendations to strengthen hazard control and improve the effectiveness and sustainability of HACCP implementation in frozen shrimp processing.